Fibrosis-4 Index Can Independently Predict Major Adverse Cardiovascular Events in Nonalcoholic Fatty Liver Disease. (18th March 2022) - Vieira Barbosa, Joana; Milligan, Scott; Frick, Andrew; Broestl, Jeremy; Younossi, Zobair; Afdhal, Nezam; Lai, Michelle
Abstract : INTRODUCTION: Nonalcoholic fatty liver disease (NAFLD) is closely associated with an increased risk of cardiovascular disease. We aimed to determine whether the fibrosis-4 index (FIB-4) can identify patients with NAFLD at highest risk of cardiovascular events. METHODS: We analyzed data from 81, 108 patients with (i) a diagnosis of NAFLD, (ii) nonalcoholic steatohepatitis (NASH), or (iii) at risk (RISK) of NASH. The outcome of interest was major adverse cardiovascular events (MACE) defined by myocardial infarction, hospitalization for unstable angina or heart failure, and coronary revascularization. RESULTS: The mean age was 62 years, and 49.6% were men. Among 67, 273 patients without previous cardiovascular disease, 9, 112 (13.5%) experienced MACE over median follow-up of 3 years. In univariate analysis, a FIB-4 ≥2.67 was a significant predictor of MACE overall (hazard ratio [HR] 1.82, 95% confidence interval [CI] 1.63–2.04, P < 0.001) and across all baseline groups. After adjusting for established cardiovascular risk factors, FIB-4 ≥2.67 remained the strongest predictor of MACE overall (adjusted HR [aHR] 1.80, 95% CI 1.61–2.02, P < 0.001) and was consistently associated with myocardial infarction (aHR 1.46, 95% CI 1.25–1.70, P < 0.001), hospitalization for unstable angina (aHR 1.24, 95% CI 1.03–1.49, P = 0.025), hospitalization for heart failure (aHR 2.09, 95% CI 1.86–2.35, P < 0.001), coronary artery bypass graft (aHR 1.65, 95% CI 1.26–2.17, P < 0.001), and percutaneous coronary intervention (aHR 1.72, 95% CI 1.21–2.45, P = 0.003). DISCUSSION: In a large, real-world cohort of patients with NAFLD, NASH, or at RISK of NASH, the FIB-4 score was the strongest independent predictor of MACE, beyond established cardiovascular risk factors and baseline liver diagnosis.